2013
DOI: 10.14260/jemds/667
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Dermatoglyphics (Finger Tip Pattern) in Patients With Myocardial Infarction and Control Group.

Abstract: BACKGROUND: Dermatoglyphics is the scientific study of epidermal ridges and their configurations on the palmar region of hand and fingers and plantar region of foot and toes. The myocardial infarction is almost always caused by coronary artery disease. Against the genetic background of dermatoglyphic patterns and coronary artery disease, the study was undertaken to determine the correlation between them. AIMS To do a comparative study of the dermatoglyphics (finger tip pattern) in patients with myocardial infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Chimne et al documented the decrease in the percentage of arches in CAD patients of both sexes and in both hands but not significant [12]. Saxena et al [13], Patloo et al [14] Kakkeri et al [15] found out lower incidence of arches in MI cases. Whorls: In the present study, the frequency of whorl is increased in MI patients (P<0.000001) when compared to controls and significantly increased in both hands (p<0.01).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Chimne et al documented the decrease in the percentage of arches in CAD patients of both sexes and in both hands but not significant [12]. Saxena et al [13], Patloo et al [14] Kakkeri et al [15] found out lower incidence of arches in MI cases. Whorls: In the present study, the frequency of whorl is increased in MI patients (P<0.000001) when compared to controls and significantly increased in both hands (p<0.01).…”
Section: Discussionmentioning
confidence: 97%
“…Chimne et al also found out the significant decrease in loop pattern in all digits of coronary artery disease (CAD) patients [12]. Saxena et al [13], Patloo et al [14], and Kakkeri et al [15] also reported (p<0.05) [12]. Dhall et al also reported significant increase in the whorls in right thumb, right little finger and left ring finger [9].…”
Section: Discussionmentioning
confidence: 99%